Over-expansion capacity and stent design model: An update with contemporary DES platforms. (15th October 2016) - Ng, Jaryl; Foin, Nicolas; Ang, Hui Ying; Fam, Jiang Ming; Sen, Sayan; Nijjer, Sukhjinder; Petraco, Ricardo; Di Mario, Carlo; Davies, Justin; Wong, Philip
Abstract: Background: Previously, we examined the difference in stent designs across different sizes for six widely used Drug Eluting Stents (DESs). Although stent post-dilatation to larger diameter is commonly done, typically in the setting of long tapering segment or left-main PCI, there is an increasing recognition that information with regard to the different stent model designs has a critical impact on overexpansion results. This study aims to provide an update on stent model designs for contemporary DES platforms as well as test overexpansion results under with oversized post-dilatation. Methods and results: We studied 6 different contemporary commercially available DES platforms: Synergy, Xience Xpedition, Ultimaster, Orsiro, Resolute Onyx and Biomatrix Alpha . We investigated for each platform the difference in stent designs across different sizes and results obtained after post-expansion with larger balloon sizes. The stents were deployed at nominal diameter and subsequently over expanded using increasingly large post dilatation balloon sizes (4.0, 5.0 and 6.0 mm at 14ATM). Light microscopy was used to measure the changes in stent geometry and lumen diameter after over-expansion. For each respective DES platform, the MLD observed after overexpansion of the largest stent size available with a 6.0 mm balloon was 5.7 mm for Synergy, 5.6 mm for Xience, 5.2 mm for Orsiro, 5.8 mm for Ultimaster, 5.5 mm for 4 mm Onyx (5.9 mm for the 5 mm XL size) and 5.8 mm for BioMatrix Chroma. Conclusion: This update presents valuable novel insights that may be helpful for careful selection of stent size for contemporary DES based on model designs. Such information is especially critical in left main bifurcation stenosis treatment where overexpansion to larger oversized diameter may be required to ensure full stent apposition.